Minimally Invasive Platforms in Biosensing - Pandey, Prem C.; Pandey, Govind; Narayan, Roger J. (Frontiers in Bioengineering and Biotechnology, 2020)
In this manuscript, recent advancements related to minimally invasive transdermal biosensing are reviewed. Many approaches have been utilized for generating minimally invasive platforms. For example, transdermal biosensing via microneedles has emerged as a novel approach for minimally invasive detection of analytes in body fluids. This review considers recent innovations in the structure and performance of minimally invasive platforms.